Pola Penggunaan Akun Instagram @quranreview dalam Meningkatkan Pemahaman Agama di Kalangan Remaja di Griya Martubung - Siddiq, Muhammad; Ritonga, Muhammad Husni; Yulia, Fatma (Lembaga Yasin AlSys, 2023)
This research aims to see how to use their pattern of using Instagram to see @quranreview, how do I ask how their usage patterns do it every day. This study uses a qualitative method with a type of field research. This study uses data collection techniques by means of interviews, observation, and documentation. The informants in this study were the Instagram account @quranreview and teenagers who were at Griya Martubunng. The results of the research conducted in this study show: that in increasing religious understanding among adolescents at griya martubung, the @quranreview Instagram account has brought many positive changes, where adolescents who follow the @quranreview account have started to be more active in discussing religion, and ask many questions about problems. - the problems they face. The use of the @quranreview Instagram account is also a source of support and inspiration for respondents in living their daily lives. In conclusion, the pattern of using the Qur'an Review Instagram account is an effective method for increasing the understanding of youth at Griya Martubung about the Qur'an and Islamic teachings. By viewing @quranreview account posts at the right times, such as after college, during work breaks, or when they have free time in the afternoon, teenagers can get the maximum benefit from the educational content that is presented. Through informative, inspirational and easy-to-understand content, youth can expand their knowledge about the interpretation of Qur'anic verses, Islamic laws, moral values, Islamic historical stories, and other relevant topics.